La recherche sur les différentes interprétations de la justice et sur le potentiel des mesures de réparation des crimes de haine - Olga Jubany; Isabelle Carles (Droit et Cultures)
Restorative Justice is a theoretical and practical paradigm on justice that focuses on resolution of conflicts and different parties’ needs, rather than on the punishment of offenders. Despite its connection to wider visions of justice systems, the application of this approach varies greatly across existing legislation and programmes, as does the understanding of Restorative Justice as a valid alternative or a complement to traditional, punitive justice. The wide range of potential restorative measures, and their key significant features as opposed to traditional trials and procedures, determine a contrast frequently seen as that of binary opposition. However, recent research among involved professionals, from which we draw upon, sheds light on a wide range of restorative measures that are already found among penal or civil procedural systems, such as mandatory sensitivity and diversity training, community work, and the reparation of direct damage. Beyond these measures, restorative encounters, victim-offender mediation, restorative conferences and circles, and the use of proxy victims and offenders are particularly promising practices due to the potential effects for all parties: a more direct and satisfactory justice experience for the victims, a focus on their wellbeing, a decrease in offenders’ recidivism, and the resolution of social and community conflicts, among others. These potential effects make restorative justice particularly well-suited for hate crimes and hate-motivated harassment and discrimination, due to frequent profound consequences for both the victims and society as a whole. Experiences such as secondary victimisation, isolation, emotional duress, and both individual and collective victim experiences may be particularly well-addressed from a restorative perspective that focuses on reparation and conflict-solving.